PERENCANAAN GEDUNG PARKIR BERTINGKAT TERPUSAT MKWU, FAKULTAS ILMU KOMPUTER, PASCASARJANA, DAN PERPUSTAKAAN UNIVERSITAS JEMBER - Muhammad Alfian Nasril Bahariansyah; Krisnamurti Krisnamurti; Willy Kriswardhana (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2021)
The total department at the University of Jember is increasing year by year. Student body accomplishment impact is increasing the number of students. Because of this increment, the number of student who rides motorcycle increase too. The impact of this increment is changing a road function in MKWU, Computer and Science Faculty, Postgraduate, and Library area at the University of Jember into a parking lot (on-street parking). Therefore, it needs to be relocated to an off-street parking facility, and in this thesis, the parking facility that used is a parking building. This final project aims to find out the capacity of the existing parking area, the capacity of an elevated parking building, and the design and specification of the parking building. The method used in this thesis is the deviation of maximum cumulative, where the in-and-out vehicle’s accumulation compared with the existing capacity and the result is used for calculation of parking accumulation, parking duration, and parking index. The value of the Parking Index for 4,36 years ahead is 51,3%<100% and the parking building able to accommodate the demand. From the parking lot requirement, it needs an area of 1155 m2 and for the circulation’s area, it needs 1125,6 m2.